Supporting multilingual learners' academic language development a language-based approach to content instruction - De Oliveira, Luciana C. (New York, NY Routledge, 2023)
A practical and comprehensive resource, Supporting Multilingual Learners' Academic Language Development: A Language-Based Approach to Content Instruction introduces an accessible language-based approach to teaching academic language to multilingual learners across the content areas. Luciana C. de Oliveira provides elementary school teachers with everything they need to know to successfully teach grade level content to multilingual learners. Chapters are organized by subject, addressing the specific language demands of teaching English language arts, social studies, mathematics, and science. Each chapter features examples of implementation in grades K - 5, practical strategies, and a wealth of tables, figures, and resources. The Language-Based Approach to Content Instruction (LACI) in this book provides teachers with a ready-to-use framework of six scaffolding elements that serves as a guide to making content accessible, enabling multilingual learners to meet the grade level standard of their peers without simplification. Aligned with WIDA and CCSS standards, this resource provides the tools and methods teachers need to support multilingual learners' academic language development in the content area classroom"--
Includes bibliographical references.
Keywords: Language experience approach in education -- United States; Multilingual education -- United States; Academic language -- Study and teaching -- United States; English language -- Study and teaching -- Foreign speakers; Language arts -- Correlation with content subjects -- United States